Biometric Identification using Facial Vein Patterns - Praveen, Sheeba; Gautam, Reshma (International Journal of Engineering and Management Research, 2025)
Biometric systems play a crucial role in personal identification, leveraging the reliability and distinctiveness of physiological or behavioral traits. Among these, vein patterns in the face have gained attention for their stability and security, offering a robust method for biometric identification. This paper focuses on advancing the field with a Face Veins Based MCMT Technique. This technique utilizes a Multi-Channel Multi-Threshold approach to enhance accuracy and reliability in identifying individuals based on their unique vein patterns. By exploring the development and application of this innovative technique, the research aims to contribute to the evolution of biometric systems, addressing challenges and improving the efficacy of personal identification technologies.